21ST CENTURY TEACHING AND SOCIAL BRANDING TRENDS - Zarrina Rakhimova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores trends in 21st-century teaching and social branding, emphasizing the evolving role of educators in a digitally connected, socially dynamic world. It examines how technology integration, digital literacy, and online platforms are reshaping pedagogical practices. The paper also delves into the concept of social branding, highlighting its implications for teacher identity, professional networking, and personal branding. It proposes strategies for building an effective online presence and engaging with educational communities. The challenges of the digital divide, information overload, and ethical considerations are also discussed as pivotal factors in the transformation of modern education.